Factors that influence performance in Olympic air-rifle and small-bore shooting: A systematic review - Spancken, S.; Steingrebe, H.; Stein, T. (PLOS ONE, 2021)
Background: Air-rifle and small-bore shooting are fascinating Olympic sports due to their unique performance requirements for accuracy and precision. Objective: The purpose of our study was to systematically research the literature to determine and summarize performance determinants in both air-rifle and small-bore shooting. Since some athletes participate internationally in both disciplines in competition, the disciplines must have some similarity in the performance structure. Therefore, we further investigated whether performance in air-rifle and small-bore shooting can be explained by the same performance determinants. Methods: We systematically searched in four databases using combined keywords relevant to performance in air-rifle and small-bore shooting. The articles included had undergone peer-review and had a) a direct relation to shooting performance, b) an indirect relation by comparing the performance of shooters of different skill levels, and c) a practical relevance (directly controllable through training). After the quality of each article was assessed, the key data were extracted and summarized. Results: The fourteen articles included achieved an average of 60 ± 14% (range 30-80%) in quality assessment. Altogether, articles covered 268 subjects (32% female), of which 19% were elite- and 28% were national-level athletes. Sixteen performance determinants were investigated, which were divided into anthropometric, technical-coordinative, physiological and psychological categories. Both in air-rifle and small-bore shooting, rifle stability and body sway were found to differ between elite- and national-level athletes. In both disciplines, body sway seemed to have no influence on shot score in elite- and national-level athletes. Similarly, heart rate did not correlate with shot score at nearly all performance levels in both disciplines. In national-level air-rifle athletes, horizontal rifle stability, aiming accuracy and aiming time were found to affect shot score. Conclusions: To be competitive at a national-level in air-rifle shooting, a highly developed aiming process is needed to achieve a high shot score. Lack of data prevented us from drawing evidence-based conclusions in elite-level air-rifle athletes and in small-bore shooting. Future research should investigate possible performance determinants both in air-rifle and in small-bore shooting, especially with elite-level athletes, to confirm or disprove existing findings. Further research should use more complex analyses to investigate the multifaceted processes associated with different performance determinants.